Sensitivity of commercial rapid test kit to pork contamination in processed foods - Putri, Riski Dwimalida; Safitra, Suciana (Journal of Halal Science and Research, 2024)
Guaranteeing halal products has now become a necessity, especially for food products. This is intended to ensure that the food produced is not contaminated with non-halal ingredients, including pork. Pork contamination in processed meat foods such as meatballs is still often found. Various tests can be done to detect the presence of pork in processed foods. One of them is a rapid test using the LFIA method. This test is widely used because it is more efficient, economical, and easy to prepare samples. A rapid pork contamination test kit (XEMA) has been circulating in Indonesia. In the research, the sensitivity of this rapid test kit was tested on processed meat foods with various concentrations of pork and variations in the main ingredients. The color test shows that the simulated samples of beef meatballs without added pork are dark greyish white, as are the simulated samples with concentrations of 1% and 10%. Meanwhile, samples with concentrations of 20% and 40% have a paler color. Meanwhile, there was no significant difference in the variation in pork concentration in meatballs with the main ingredients of chicken and fish. For smell and texture, there were no significant differences in the simulated samples, both the control and samples with varying concentrations. From testing, it is known that the test kit can detect the presence of pork up to a concentration of 10% in samples, with the main ingredients being beef, chicken, or fish. These results indicate that this rapid test kit can well detect pork contamination in processed food samples.